Management Of Sports Facilities and Equipment in Physical Activities According to Saudi Vision 2030 - Dr. SAMEER MOHAMMED SAYYD; Arie Asnaldi; Zainal Abidin bin Zainuddin; Amal Mohammed Nahary (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
The purpose of this paper is to investigate the level of the availability of sports facilities and equipment in Saudi Arabia Universities with a view to exploring the extent to which it affects the students' participation in sports and physical activities. In addition, the study sought to find out if there was a need to improve the facilities and equipment based on the existing situation. As a result, 643 undergraduate students of various ages who were randomly chosen from 25 universities in Saudi Arabia had their data collected using a questionnaire. In the end, findings show that facilities and equipment were some of the factors affecting the students' participation in sports and physical activities as it was overwhelmingly agreed by the students that there was an important need to improve the availability and accessibility of the sports facilities and equipment in their institutions. Based on these results, it can be concluded that adequate attention should be given to the provision of adequate sporting facilities and equipment in order that students are encouraged to take active participation in sports and physical activities, the benefits of which cannot be overemphasized.